Obsessing about uncertainty? - Scholl, J; Rushworth, M (Cell Press, 2017)
A striking observation in obsessive-compulsive disorder is that patients know that their obsessions and compulsions are excessive, but their symptoms nevertheless persist. Drawing on computational models from basic neuroscience, Vaghi and colleagues (2017) suggest a quantitative account of this clinical finding.